Hubungan Tekstur Urat Kuarsa dan Kimia Bijih Endapan Emas Epitermal di Daerah Mekarbakti, Kecamatan Bungbulang, Kabupaten Garut, Provinsi Jawa Barat - Satriadi Abdullah; Arifudin Idrus; Nurkhamim Nurkhamim; Rangga Bintang Ardaraja (PROGRAM STUDI TEKNIK GEOLOGI FAKULTAS TEKNOLOGI MINERAL UPN VETERAN YOGYAKARTA, 2023)
Gold deposits in the West Java area, especially South Garut, enter the hydrothermal system due to Quaternary volcanic activity (Gaffar, 2017). Quartz is the main component of hydrothermal system deposits. Quartz veins have an important role in texture formation which can be used to determine the formation process and texture correlation with ore minerals (Dong et al, 1995). Quartz texture relationship in the study area is interesting to study because it becomes a reference in determining the prospect zone for the presence of precious metals as well as a reference for further exploration. For this reason, the purpose of this study was to determine the relationship between quartz texture and the presence of precious metals and base metals in the study area. The research area is in the Mekarbakti Village area, Bungbulang District, Garut Regency, West Java Province. The study area is included in the Jampang formation which is not aligned with the younger undecomposed unit (Qtv), the lithology of the study area is andesite lava, andesite breccia, lapilli, tuff, andesite intrusion and volcanic deposits. This study uses 3 methods, namely detailed field observations, ore microscopy analysis on seven samples DER_004, DER_005, DER_031, DER_001, DER_003, DER_014, DER_030 and analysis of Fire Assay Atomic Absorption Spectrophotometry (FA-AAS) and Inductively Coupled Plasma – Optical Emission Spectrometry. (ICP-OES) on seven samples DC_000087, DC_000073, DC_000030, DC_000053, DC_000048, MC_000081, DC_000082. From the results of field activities and laboratory analysis, the texture of the research area is divided into seven textures, namely cockade, lattice bladed, saccharoidal, banded comb, brecciated, colloform. The geochemistry of the ore in the study area has a fairly high grade and is associated with quartz vein textures, including brecciated Au texture 3.21 ppm, Ag 74.7 ppm, collorform Au texture 2.605 ppm, Ag 22.9 ppm, lattice bladed Au texture 1.625 ppm, Ag 2.3 ppm, saccharoidal Au texture 1.465 ppm, Ag 1.2 ppm, banded texture Au 1.257 ppm, Ag 2.3, cockade texture Au 0.079 ppm, Ag 2.7 ppm and comb texture Au 0.021 ppm, Ag 1 ppm, on the texture the presence of precious metals was observed and abundant base metals. The texture of the quartz veins in the study area, when compared with the calcifications of Morison, et al 1990, falls into the crystalline quartz zone and the crusstiform – colloform zone.